Effects of JIT, TQM Competences and Product Design on Financial Performance of the Firm: Does Supply Chain Moderates? - Nikita Indi Kumala; Suherman Rosyidi (International Journal of Supply Chain Management, 2020)
The aim linked with the ongoing literature is to analyze the influence of new product design, TQM competences and just-in-time inventory system on the financial performance of the manufacturing companies in Indonesia. The objectives also include the examination of the moderating role of supply chain management among the links of new product design, TQM competences, just-in-time inventory system and financial performance of the manufacturing companies in Indonesia. The data was obtained by using questionnaires while analysis was conducted by using smart-PLS. The results exposed that new product design, TQM competences and just-in-time inventory system have positively associated with the financial performance of the manufacturing companies in Indonesia. The findings also showed that supply chain management positively moderated among the links of TQM competences and financial performance. These results are beneficial for the new researchers who want to investigate it further along with the regulators who want to develop policies related to the supply chain, TQM and firm performance.